2008
DOI: 10.3892/ijmm.21.6.825
|View full text |Cite
|
Sign up to set email alerts
|

Murine intramyocellular lipids quantified by NMR act as metabolic biomarkers in burn trauma

Abstract: Abstract. It has been suggested that intramyocellular lipids (IMCLs) may serve as biomarkers of insulin resistance and mitochondrial dysfunction. Using a hind-limb mouse model of burn trauma, we tested the hypothesis that severe localized burn trauma involving 5% of the total body surface area causes a local increase in IMCLs in the leg skeletal muscle. We quantified IMCLs from ex vivo intact tissue specimens using High-Resolution Magic Angle Spinning (HRMAS) 1 H NMR and characterized the accompanying gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…Meanwhile, decreased expression of PGC-1ß appears to: a) upregulate UCP3, leading to uncoupling and reduced ATP synthesis rate; and b) alter immuno-inflammatory gene expression in skeletal muscle [in cachexia Fig. 1; in experimental burn injury (31,33,34,36)]. This supposition is in agreement with other studies suggesting that upregulation of mRNA and protein expression of UCP2 and UCP3 (1214) correlates directly with antioxidative capacity (15,16) in response to elevated TNFα-induced ROS production in cancer (60).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, decreased expression of PGC-1ß appears to: a) upregulate UCP3, leading to uncoupling and reduced ATP synthesis rate; and b) alter immuno-inflammatory gene expression in skeletal muscle [in cachexia Fig. 1; in experimental burn injury (31,33,34,36)]. This supposition is in agreement with other studies suggesting that upregulation of mRNA and protein expression of UCP2 and UCP3 (1214) correlates directly with antioxidative capacity (15,16) in response to elevated TNFα-induced ROS production in cancer (60).…”
Section: Discussionmentioning
confidence: 99%
“…We also propose that it is complementary to NMR, which has already shown the consequences of bioenergetic and mitochondrial dysfunction in vivo (22)(23)(24)(25). Thus, our results lead us to conclude that bioenergetic dysfunction and insufficient oxidative defense following local burn trauma may lead to oxidative damage.…”
Section: Discussionmentioning
confidence: 68%
“…In addition to NMR spectroscopy, the development of highthroughput microarray systems, capable of simultaneously measuring the expression of thousands of genes, has also greatly advanced our ability to detect and measure biomarkers. By exploring the expression of certain organ-specific candidate genes, the biological relevance of NMR data can be validated in microarray experiments examining the same specimen (22,23,25). For assessing oxidative damage after burn trauma, in vivo EPR using nitroxides is complementary to NMR since NMR cannot measure redox status and reactive oxygen species (ROS), while EPR can.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies of 1 H MRS combined with ex vivo HRMAS 1 H MRS have revealed intramyocellular lipids (IMCLs) in rodents (11,17), while other ex vivo HRMAS 1 H MRS studies have focused on lipid metabolism (18). Szczepaniak et al demonstrated that IMCL stores could be quantified accurately in a clinical setting by 1 H NMR spectroscopy in vivo (19).…”
Section: Introductionmentioning
confidence: 99%